Analisis Perubahan Penutupan Lahan Menggunakan Citra Resolusi Tinggi di Kecamatan Nagrak, Kabupaten Sukabumi (Land Cover Change Analysis Using High-Resolution Imagery in Nagrak Sub-district, Sukabumi District) - Syahrul Ramdan; Muhammad Buce Saleh; Nining Puspaningsih (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2025)
Land cover change is a global phenomenon influenced by social, economic, and governmental policy dynamics. Nagrak District, located around Mount Gede Pangrango National Park, has experienced significant changes due to policy shifts and population growth. This study aims to classify land cover classes, compare the classification methods used, and analyze land cover changes from 2017 to 2022. The methods used in this study include visual and digital classification. Visual classification using the on-screen digitizing method produced nine land cover classes with an accuracy of 94%, while digital classification using the random forest algorithm resulted in 89% accuracy. To improve accuracy, the results of both classifications were combined using the identity method, resulting in better and more accurate land cover classes. The analysis results show a positive change of 54,17 ha (0,78%), reflecting an increase in land function from unproductive to productive. Conversely, a negative change of 214,08 ha (3,10%) indicates pressure on land sustainability. This study provides an overview of land use dynamics, which can inform spatial planning and sustainable resource management.